Functional Assays for Classification of BRCA2 Variants of Uncertain Significance - Farrugia, Daniel J. (2008)
The assessment of the influence of many rare BRCA2 missense mutations on cancer risk has proved difficult. A multifactorial likelihood model that predicts the odds of cancer causality for missense variants is effective, but is limited by the availability of family data. As an alternative, we developed functional assays that measure the influence of missense mutations on the ability of BRCA2 to repair DNA damage by homologous recombination and to control centriole amplification. We evaluated 22 missense mutations from the BRCA2 DNA binding domain (DBD) that were identified in multiple breast cancer families using these assays and compared the results with those from the likelihood model. Thirteen variants inactivated BRCA2 function in at least one assay; two others truncated BRCA2 by aberrant splicing; and seven had no effect on BRCA2 function. Of 10 variants with odds in favor of causality in the likelihood model of 50:1 or more and a posterior probability of pathogenicity of 0.99, eight inactivated BRCA2 function and the other two caused splicing defects. Four variants and four controls displaying odds in favor of neutrality of 50:1 and posterior probabilities of pathogenicity of at least 1 × 10(−3) had no effect on function in either assay. The strong correlation between the functional assays and likelihood model data suggests that these functional assays are an excellent method for identifying inactivating missense mutations in the BRCA2 DBD and that the assays may be a useful addition to models that predict the likelihood of cancer in carriers of missense mutations.